2018
DOI: 10.1210/jc.2018-00889
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Levels in Third Trimester in Polycystic Ovary Syndrome: Odense Child Cohort

Abstract: TT and FT levels were higher in third-trimester pregnant women with PCOS compared with controls. Separate reference interval for FT in women with PCOS should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…Women with PCOS have higher testosterone levels during pregnancy compared with women without PCOS. This finding is in line with previous studies in pregnant women with PCOS, in which high testosterone levels also in late pregnancy have been noted (Glintborg et al, 2018;Detti et al, 2019;Piltonen et al, 2019). In pregnancy, maternal testosterone levels depend mainly on the feto-placental unit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women with PCOS have higher testosterone levels during pregnancy compared with women without PCOS. This finding is in line with previous studies in pregnant women with PCOS, in which high testosterone levels also in late pregnancy have been noted (Glintborg et al, 2018;Detti et al, 2019;Piltonen et al, 2019). In pregnancy, maternal testosterone levels depend mainly on the feto-placental unit.…”
Section: Discussionsupporting
confidence: 92%
“…Findings on the role of hyperandrogenism for the obstetric complications that women with PCOS may encounter are less conclusive, as these also seem to depend on PCOS phenotype and maternal ethnicity, but only a few high-quality studies have been published (Falbo et al, 2010;Palomba et al, 2010;Bahri Khomami et al, 2018). Women with PCOS have higher total testosterone and free androgen index during pregnancy (Glintborg et al, 2018;Valdimarsdottir et al, 2019), and testosterone levels are positively correlated with AMH levels (Detti et al, 2019;Piltonen et al, 2019;Valdimarsdottir et al, 2019). The specific role of testosterone in the development of obstetric and neonatal complications has been assessed in a relatively limited number of studies, but rarely in PCOS populations.…”
mentioning
confidence: 99%
“…This increase in SHBG is paralleled by higher circulating total testosterone levels, keeping free testosterone within the normal range of non-pregnant women until 3 rd trimester (Bammann et al, 1980). In women with PCOS, free testosterone levels increase during 3 rd trimester, which result in higher levels of free testosterone in women with PCOS compared to controls (Bammann et al, 1980;Glintborg et al, 2018). Elevated testosterone levels during pregnancy in women with PCOS question the complete suppression of ovarian and adrenal activity during pregnancy in PCOS (Caanen et al, 2016;Kallak et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…In agreement with these findings, women with PCOS often give birth to babies smaller for gestational age and pregnant women with the syndrome experience elevated androgen levels and placental dysfunction. 45,46 It is also known that adverse maternal environmental exposures can alter the fetal epigenome. 47 In the present study, we showed an altered expression of maternal imprinting genes not only in the 17NF placentae at E18.5 but also in both the fetal and adult 17NF ovaries.…”
Section: Discussionmentioning
confidence: 99%